Cerebral Blood Flow Thresholds for Tissue Infarction in Patients with Acute Ischemic Stroke Treated with Intra-Arterial Revascularization Therapy Depend on Timing of Reperfusion - Mui, K.; Yoo, A.J.; Verduzco, L.; Copen, W.A.; Hirsch, J.A.; González, R.G.; Schaefer, P.W. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: MR perfusion CBF values can distinguish hypoperfused penumbral tissue likely to infarct from that which is likely to recover. Our aim was to determine if CBF thresholds for tissue infarction depend on the timing of recanalization in patients with acute stroke treated with IAT. MATERIALS AND METHODS: Twenty-six patients with acute proximal anterior circulation strokes underwent DWI and PWI before IAT. rCBF was obtained in the following areas: 1) C with abnormal DWI, reduced CBF, follow-up infarction; 2) PI with normal DWI, reduced CBF, follow-up infarction and 3) PNI with normal DWI, reduced CBF, normal follow-up. rCBF in tissue reperfused at <6 hours (early recanalizers), in tissue reperfused at >6 hours (late RC), and in NRC was compared. RESULTS: For C, mean rCBF was 0.13 (SEM, 0.002), 0.29 (0.007), and 0.21 (0.004) for early recanalizers, late recanalizers, and nonrecanalizers, respectively (P < .001, for all comparisons). For PI, mean rCBF was 0.34 (0.006), 0.38 (0.008), and 0.39 (0.005) for early recanalizers, late recanalizers, and nonrecanalizers, respectively (P < .001 for early-versus-late recanalizers and versus nonrecanalizers; P > .05 for late recanalizers versus nonrecanalizers). For PNI, the mean rCBF was 0.38 (0.002), 0.48 (0.003), and 0.48 (0.004) for early recanalizers, late recanalizers, and nonrecanalizers, respectively (P < .001 for early-versus-late recanalizers and nonrecanalizers; P > .05 for late recanalizers versus nonrecanalizers). ROC analyzis demonstrated optimal rCBF thresholds for tissue infarction of 0.27 (sensitivity, 80%; specificity, 87%), 0.44 (sensitivity, 77%; specificity, 75%), and 0.41 (sensitivity, 78%; specificity, 77%) for early recanalizers, late recanalizers, and nonrecanalizers, respectively. CONCLUSIONS: CBF thresholds for tissue infarction in patients with acute stroke are lower in tissue that is reperfused at earlier time points. This information may be important in selecting patients who might benefit from reperfusion therapy. AISacute ischemic strokeAUCarea under the ROC curveCinfarct coreCBFcerebral blood flowCBVcerebral blood volumeDWIdiffusion-weighted imagingFLAIRfluid-attenuated inversion recoveryIATintra-arterial therapyICAinternal carotid arteryIVintravenousMCAmiddle cerebral arteryMTTmean transit timeOOPoptimal operating pointPIpenumbra that infarctsPNIpenumbra that does not infarctPWIperfusion-weighted imagingrCBFrelative cerebral blood flowROCreceiver operating characteristic analysisSEstandard errorSEMstandard error of the meanTonsettime from stroke onset to vessel recanalizationtPAtissue plasminogen activator